Impacto de una recesión estadounidense en la economía peruana: ¿somos más o menos vulnerables? - Rabanal B., Violeta Alexandra (2009)
This document attempts to evaluate the strength and weaknesses of the Peruvian economy when facing external shocks, specifically a contraction in the US output. For this purpose, an analysis of the vulnerabilities’ sources is made through the revision of relevant indicators; after that, the main transmission channels are raised and an econometric exercise using the structural vector autoregressive methodology is developed to simulate the effects of a shock in US economy. The main conclusion is that even though the country shows an important trengthening in many relevant aspects such as financial strength indicators and export diversification, in its position of a small and open economy, it remains exposed to external shocks. Nevertheless, it is clear that the actual position of Peruvian economy is more favorable. In this way, it has been demonstrated that Peru can maintain a growth rate of 6%, facing a deceleration of US economy of two percentage points.